1996
DOI: 10.1088/0963-6625/5/2/002
|View full text |Cite
|
Sign up to set email alerts
|

The thrill of everyday science: images of science and scientists on children's educational science programmes in the United States

Abstract: Several media effects perspectives suggest that televised images can influence children's perceptions of science and scientists. This study analysed images of science and scientists in four children's educational science programmes. The images of science as truth, as fun, and as a part of everyday life, as well as the image that science is for everyone, were quite evident. Little evidence was found for the image of science as magical or mysterious. Support for the images of science as dangerous and science as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
2
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 18 publications
1
42
2
4
Order By: Relevance
“…For example, the show's lead character was humanized in terms of his penchant for quips (the show's pre-credits sequence often ended with him making one) and his outrage at violence toward children (as in "Gentle, Gentle," when he found a murdered baby). In some ways, the show echoed common media stereotypes of scientists (see, e.g., Long and Steinke, 1996;Long et al, 2001;Steinke, 2005). Most obviously, it depicted the white, male, middle-aged head of the crime lab as calm, rational, detached, and eccentric (particularly in his fondness for insects).…”
Section: Dna Testing and Models Of Forensic Scientistsmentioning
confidence: 83%
See 1 more Smart Citation
“…For example, the show's lead character was humanized in terms of his penchant for quips (the show's pre-credits sequence often ended with him making one) and his outrage at violence toward children (as in "Gentle, Gentle," when he found a murdered baby). In some ways, the show echoed common media stereotypes of scientists (see, e.g., Long and Steinke, 1996;Long et al, 2001;Steinke, 2005). Most obviously, it depicted the white, male, middle-aged head of the crime lab as calm, rational, detached, and eccentric (particularly in his fondness for insects).…”
Section: Dna Testing and Models Of Forensic Scientistsmentioning
confidence: 83%
“…Similarly, the "drench hypothesis" (Greenberg, 1988; see also Long et al, 2001) suggests that favorite characters can shape viewers' thoughts, beliefs, and actions. Previous studies have drawn on social cognitive theory to argue that depictions of science and scientists in educational programming and popular films may influence children's attitudes, beliefs, and behaviors regarding science and scientists (Long and Steinke, 1996;Long et al, 2001;Steinke, 2005).…”
Section: Toward a Theoretical And Empirical Foundation For Studying Tmentioning
confidence: 99%
“…Despite this argument, film research suggests that movies and television viewing experiences often lead to a changed perception or understanding of science or a scientific phenomena (Frank, 2003) despite the fact that audience members are aware that they are watching entertainment. The research base has shown that movies do have an impact on citizens' conceptions of science by either encouraging excitement, instilling fear about science and technology, or by leading to the development of stereotypes of science and scientists (Cavanaugh and Cavanaugh, 1996;Long and Steinke, 1996). Movies also have an impact by increasing the public's belief in paranormal phenomena (Sparks, 1998;Sparks et al, 1997), and by propagating a masculine view of science (Steinke, 1999).…”
Section: Analytic Framework: Science and Film Theorymentioning
confidence: 99%
“…Television programmes aimed at children are another possible source of student perceptions and later adult stereotypes. Long and Steinke (1996) analysed four educational television programmes in the USA. They concluded: 'In general, the children's programs reinforce helpful images of scientists (e.g., science is fun, scientists are elite), while minimizing the harmful images (e.g., scientists are evil)' (p. 116).…”
Section: Portrayals Of Science and Scientists: Fictional Mediamentioning
confidence: 99%